2018
DOI: 10.15441/ceem.16.188
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital i-gel blind intubation for trauma: a simulation study

Abstract: ObjectiveThis study aimed to evaluate the efficacy of i-gel blind intubation (IGI) as a rescue device for definitive airway management in ground intubation for pre-hospital trauma patients.MethodsA prospective randomized crossover study was conducted with 18 paramedics to examine intubation performance of two blind intubation techniques through a supraglottic airway devices (IGI and laryngeal mask airway Fastrach), compared with use of a Macintosh laryngoscope (MCL). Each intubation was conducted at two levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Therefore, it is crucial to search for methods of endotracheal intubation alternative to direct laryngoscopy. These include SADs, with a possibility to perform blind intubation by using the SAD ventilation channel as a guide for the endotracheal tube [16, 21]. In the presented study, the first attempt effectiveness with all the tested devices exceeded 71%, being the highest with the iGEL mask (85.3%).…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, it is crucial to search for methods of endotracheal intubation alternative to direct laryngoscopy. These include SADs, with a possibility to perform blind intubation by using the SAD ventilation channel as a guide for the endotracheal tube [16, 21]. In the presented study, the first attempt effectiveness with all the tested devices exceeded 71%, being the highest with the iGEL mask (85.3%).…”
Section: Discussionmentioning
confidence: 79%
“…17 Several studies have shown that the SAD is quick to insert and is effective as an airway management device across a wide variety of different prehospital airway encounters. [18][19][20] The manufacturer indicates that the device can be in place for up to four hours, well exceeding most EMS transport times. 21 In this protocol, a paralytic (rocuronium) was intended to be delivered only when two post-induction attempts at placement were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the nature of blind technique of IGI, the success rate for IGI has been reported from 75% to 100% despite the high speed of IGI [16, 18]. To improve the success rate of IGI, we need to apply counterclockwise rotation technique [11, 19].…”
Section: Discussionmentioning
confidence: 99%